Analysis of the adequacy of judicial activismto the Brazilian constitutional structure: a perspective based on the moral reading of the constitution proposed by Ronald Dworkin (Revista Paradigma, 2023)
This article deals with analyzing the appropriateness of the behavior conventionally known as "judicial activism" to the Brazilian constitutional structure, taking as background the moral reading of Constitution developed by Ronald Dworkin's. The concepts will be related in order to answer the following question: Does judicial activism present itself as a necessary consequence of the concretion activity of the Constitution exercised by the Supreme Court? To this end, issues related to Dworkin's theory, the concept of judicial activism and the theoretical foundation of activism in Brazil will be exposed. It will be concluded that, despite the fact that the interpretation of the constitutional text inevitably involves moral judgments, judicial activism is not a necessary consequence of constitutional jurisdiction. On the contrary, judicial activism, as defined in this text, is a dysfunctionality of the constitutional justice system, which distances it from the activity of concretizing the text of the Constitution.